Production and evaluation of a chromatographically purified vero cell rabies vaccine (pvrv) in china using microcarrier technology - Tang, Q.; Yu, P.; Huang, Y.; Zhang, Y.; Liang, G. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
China is a high population country with millions of animal bite cases every year; thus, it is necessary to explore and develop more effective and productive rabies vaccines for human use. To establish a safe, effective, inexpensive and high-yield rabies vaccine, a non-adjuvant purified Vero cell rabies vaccine produced in the SPEEDA PVRV microcarrier bioreactor was developed by Liaoning Chengda Biology Co. Ltd. in China. This vaccine was produced using Vero cells that were cultured in a microcarrier bioreactor. A microcarrier bioreactor containing 25 g/L of Cytodex-1 was used for perfusion culture. The Vero cell culture density was up to 1.2–1.5 × 107 cells/ml, viruses could be constantly harvested for 18–22 d, and the resulting vaccine immunizing potency was ≥ 4.5 IU/ml. Vaccine safety and immunogenicity post-immunization were also assessed. A total of 602 volunteers were enrolled and divided into two groups that were vaccinated with either SPEEDA PVRV or VERORAB PVRV on days 0, 3, 7, 14 and 28. All subjects vaccinated with SPEEDA PVRV showed no serious local or systemic adverse effects. The positive conversion rate of serum neutralizing antibodies against the rabies virus reached 100% in both the test and control groups (inoculated with VERORAB PVRV) at 14 d and 45 d after vaccination, and no significant difference was found between the neutralizing antibody geometric mean titers (GMTs) of the two groups. SPEEDA PVRV is appropriate for mass production and shows satisfactory clinical safety and immunogenicity for human post-exposure prophylaxis of rabies.